Optimalisasi Kompetensi Guru dalam Mendukung Kebijakan Profil Pelajar Pancasila - Muchamad Arif Kurniawan; Pirman Pirman; Siti Rosmiyati (LPMP Imperium, 2024)
This community service program aims to optimize the enhancement of teacher competencies at MTs Tarbiyatul Huda Bogor to support the implementation of the Pancasila Student Profile Policy. The activities were conducted on June 14-15, 2024, and are considered crucial in shaping students with Pancasila characteristics, namely being faithful and pious to God Almighty, having noble character, being independent, critical thinkers, creative, collaborative, and globally-minded. The program involved a series of training sessions focused on improving teachers' understanding and skills in integrating Pancasila values into the teaching process. The method used was Participatory Action Research (PAR), which includes the stages of To Know, To Understand, To Plan, To Act, and To Change. The results of this program indicate an improvement in teachers' competencies in designing and implementing lessons aligned with Pancasila values. Additionally, there was an increase in teachers' motivation and enthusiasm for integrating Pancasila values into the curriculum and school activities. It is expected that strengthening teacher competencies will positively impact the quality of education and the formation of student character in line with the Pancasila Student Profile. The program was evaluated through questionnaires completed by the teachers, with findings indicating the program's success in enhancing the quality of education and the relevance of Pancasila values at MTs Tarbiyatul Huda Bogor.